Determining sources of groundwater salinity in the multi-layered aquifer system of the bengal delta, Bangladesh - Zahid, Anwar; Rahman, Aminur; Hassan, M. Rashidul; Ali, M. Hazrat (© 2016 Published by BRAC University, 2017)
This article was published in the BRAC University Journal [© 2016 Published by BRAC University].